Are You Sure Your Software Will Not Kill Anyone? Using software to control potentially unsafe systems requires the use of new software and system engineering approaches. - Leveson, Nancy (Communications of the ACM, 2020)
The article explores computers and their use in the control of safety-critical systems. The author notes that, with few exceptions, software was not directly controlling safety-critical systems until approximately 1980. A diagram is provided of a cyber-human-physical control loop and accidents involving computers, including those involving aircrafts, are described.